Government Mobile Apps: Analysing Citizen Feedback via App Reviews - Aamir, Tooba; Chhetri, Mohan Baruwal; Chamikara, M.A.P.; Grobler, Marthie (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2023)
Governments worldwide are increasingly embracing digital transformation initiatives to enhance service delivery, engage citizens, and achieve better outcomes. However, obtaining continuous feedback on these initiatives poses a substantial challenge. This paper investigates the feasibility of leveraging mobile app reviews as a valuable source of citizen feedback on government digital services. We analyse 100,146 app reviews from 129 government mobile apps in Australia and identify several functional and usability issues. These include issues such as app instability, complexity, integration problems, navigation difficulties, inaccuracies, and challenges with ID verification and authentication processes. Furthermore, we uncover several factors that influence user satisfaction, including accuracy and reliability, convenience, dependability, user-centric design, and overall user-friendliness. These findings demonstrate a strong correlation between user feedback and the government's digital transformation strategy, underscoring the viability of mobile app reviews as a cost-effective avenue for collecting citizen feedback.